Pengaruh Penggunaan Media Video Animasi Terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Siswa Kelas III SDN 06 Sungai Raya - Andini, Nabila Shafa (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the extent to which animated videos affect students learning outcomes at SDN 06 Sungai Raya Class III of thematic learning. This study used a Quasi-Experimental and quantitative nature. Learning outcomes are bound variables (Y), while animation video media are free variables (X). The population of this study is grade III students of SDN 06 Sungai Raya. The sample taken was 18 students from each class III A and III B as a research sample for the experimental class and the control class. The sampling technique used is Saturated Sampling. The instrument used in data collection is a test that measures student learning outcomes in thematic learning. The independent sample t-test is used in the findings of data analysis after normality and homogeneity have been established. Based on statistical data, the effect between the experimental class that used animated video with Sig (2-tailed) and the control class that used lap book media was 0.000 < 0.05. As is known, in KKM 67, the average score of the experimental class was 79.72 better than the average score of the control class of 66.39